PARADIGMA DAN STRATEGI DAKWAH HUMANIS PADA KOMUNITAS MINORITAS (Studi Kasus Kaum Waria di Kota Kudus) - Rosyid, Moh (Universitas Islam Negeri Raden Intan Lampung, 2012)
The existence of a community, wherever it my be, if it were looked as dissimilar as their environment, especially those of minorities, has always had a minor response from the communities of majority. This is exactly experienced by the transgender community. Those of transvestites are being viewed negatively due to the irregularities in the way they live and behave. This article tries to formulate a model of humanistic proseltizing that is not against the existence of such transgender community as objects of the proselytizing (mad’u). Based on a research on the portrait of transvestites in the city of Kudus, Central Java, the author suggests that if the notion to proportionally placed transvestites is overlooked or that the transgender community is out of consideration for being targeted community (mad’u), then we basically have missed the humanistic character of the mission itself. The existence of transgender in a religious observance is, indeed, indifference as those of non-transgender community that needs touches of religious values by a preacher. Denial of human existence to those of transgender (the humanist character) is fundamentally at odds with the mandate of Law Number 39 Year 1999 on Human Rights. If this is the case, then, it needs to takes that of humanistic proselytizing approach which humanize all human beings, including those of transvestites.